Archaeology, cultural heritage, and the antiquities trade (Cultural heritage studies, 2006)
A collection of essays, this work investigates the ways that commodifying artifacts fuels the destruction of archaeological heritage and considers what can be done to protect it. It argues that the antiquities market impacts cultural heritage around the world and is a burgeoning global crisis